PENGUATAN LITERASI MEMBACA MELALUI MEDIA CERITA BERGAMBAR PADA SISWA SEKOLAH DASAR - Nurrahmi; Azrina Ratna Masriani; Dwi Astuty; Intan Nuraini; Wulan Regina Putri; Syafruddin Muhdar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the implementation of picture story media in strengthening reading literacy among elementary school students at SD Aisyiyah 1 Mataram. The study is motivated by the low level of reading interest and limited student participation in classroom learning. A qualitative descriptive approach was employed, with data collected through observation and documentation. The findings indicate that picture story media plays a significant role in fostering students’ engagement, reading interest, collaboration, and self-confidence. Students are more actively involved in reading activities, observing visual elements, participating in discussions, and presenting their ideas. In addition, their ability to comprehend and retell stories improves. The learning environment becomes more dynamic and student-centered. However, several challenges were identified, including limited instructional time, variations in students’ reading abilities, and a lack of confidence among some learners. Overall, picture story media is considered an effective strategy for strengthening reading literacy in elementary education.